GAMBARAN TINGKAT STRES PADA PASIEN DIABETES MELLITUS (DM) TIPE 2 - Zuliani, Zuliani; Fatmawati, Diah Ayu; Nisa, Nurul Khoirun; Nurmalisyah, Fitri Firanda (Universitas Pesantren Tinggi Darul Ulum, 2023)
Diabetes Mellitus patients experience chronic metabolic disorders characterized by increased blood glucose due to several factors. Stress is one factor that can cause blood sugar levels to increase. The aim of this research is to determine the description of stress levels in people with type 2 diabetes mellitus. This research used a descriptive design. The place of this research is in the Humaira Room at PMC Hospital. The research sample was taken by non-probability sampling with random sampling technique. The data collection process using two DASS 42 was applied with a rating scale format. The stress levels in this study were normal, light, moderate, severe, very severe, to determine the level of stress in diabetes mellitus patients with a total of 14 questions. Data analysis used univariate. The results of this study were mostly male, namely 17 people (56.7%) and aged 40-60 years. Most of the respondents had no school education, no work and had suffered from diabetes mellitus < 5 years. Respondents experienced mild stress levels of 8 respondents (26.7%), moderate stress 19 respondents (63.3%) and severe stress 3 respondents (10%). The most serious source of stress comes from within themselves, namely, feeling that diabetes controls their life. Another source of stress still comes from outside but originates from interpersonal or relationships with others, sufferers feel that friends and family lack support and respect in treating diabetes mellitus. Therefore, they really need support from family and those closest to them. Keywords: Stress level, Diabetes mellitus patients, Chronic diseases.